Straightforward synthesis of dipyrido-annelated NHC-Palladium(II) complexes by oxidative addition: dedicated to Robert Weiss on the occasion of his 70th birthday - Gierz, Verena; Rominger, Frank (European journal of inorganic chemistry, 2012)
A straightforward synthesis method for mixed phosphane dipyrido-annelated N-heterocyclic carbene (dipiy) palladium(II) complexes is presented. The key step is the oxidative addition of 6-bromodipyridoimidazolium bromides that can be prepared easily from dipyridine in a two step reaction. This new procedure avoids any generation of the free carbene as well as any transmetallation step.